1977
DOI: 10.1002/j.1556-6978.1977.tb01061.x
|View full text |Cite
|
Sign up to set email alerts
|

A Course on Counseling Ethnic Minorities: A Model

Abstract: There is a need for content courses and practicum experiences in the area of counseling ethnic minorities in counselor education departments across the country. Generally, the only preparation that counselor trainees and others receive in this important area is provided through workshops and conferences, since few such formal courses exist today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Strupp (1973) has observed that culturally conditioned attitudes may be evoked in helpers by the client's socioeconomic status, sex, cultural background, and color. Many contend that, as generally practiced, counseling and psychotherapy are oriented toward the White middle-class client (Atkison, Morten, & Sue, 1979) whose values, stan- dards, and expectations may not apply equally to non-White, poor, or "third world" groups (Goldstein, 1981;McDavis & Parker, 1977). The emphasis placed on intrapsychic causation and personal or family disorganization, often to the exclusion of societal and institutional dysfunction, is considered to be particularly detrimental to the poor and to racial minorities (Berman, 1979;Block, 1981;Bryson & Bardo, 1975).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Strupp (1973) has observed that culturally conditioned attitudes may be evoked in helpers by the client's socioeconomic status, sex, cultural background, and color. Many contend that, as generally practiced, counseling and psychotherapy are oriented toward the White middle-class client (Atkison, Morten, & Sue, 1979) whose values, stan- dards, and expectations may not apply equally to non-White, poor, or "third world" groups (Goldstein, 1981;McDavis & Parker, 1977). The emphasis placed on intrapsychic causation and personal or family disorganization, often to the exclusion of societal and institutional dysfunction, is considered to be particularly detrimental to the poor and to racial minorities (Berman, 1979;Block, 1981;Bryson & Bardo, 1975).…”
mentioning
confidence: 99%
“…Despite the dearth of research in cross-cultural counseling, a review of the literature reveals that a number of assumptions exist. For example, it is assumed that: (a) perceptions detrimental to cross-cultural counseling are learned and can be altered (McDavis & Parker, 1977;Truax & Carkhuff, 1969); (b) knowledge and understanding of the client's culture and perceptions are prerequisites for effective counseling (Smith et al, 1978); (c) the level of expressed counselor empathy is paramount, and it is influenced by the counselor's perception of the client's dissimilarity (Bryson & Bardo, 1975;Harrison, 1975); and (d) counselor anxiety may interfere with counselor effectiveness (Bowman & Giesen, 1982), particularly during cross-cultural encounters (Block, 198 1 ;Vontress, 1974).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, participants complain about a comparative overload of teaching input and a lack of opportunity to discuss, digest and reflect. This echoes the point by Gibbs (1981) and McDavis and Parker (1977) that a single experience like this is insufficient to have a lasting effect on professional development. Hui participants themselves stress the need to obtain more information about Maori adjustment, available community resources, and principles of cross-cultural counselling; they also want specific training in the cross-cultural application of various professional skills taught.…”
Section: Discussion and Evaluationmentioning
confidence: 89%
“…There are exceptions, of course-a few isolated courses on intercultural counseling issues offered at some universities. But the scope of such courses is usually limited to selected ethnic minorities (e.g., McDavis & Parker, 1977).…”
Section: Need For Comparative Studies In Guidancementioning
confidence: 99%